Analysis Influence Go-Food Plus Member Promotion and Service Quality on User Loyalty in the Go-Jek Application - Lestari, Mentari Puji; Andara, Melisa Dwi; Wadhwa, Sunny (Proceeding International Conference on Information Technology and Business, 2023)
The aim of this research is to analyze the influence of promotions, service quality and user loyalty on the Go-Jek application. Mediating variables and to find out the most dominant variables on promotion, service quality and user loyalty on the Go-Jek application. The analytical method in this research uses quantitative methods, descriptive analysis methods . The test stage carried out was a data analysis test in this research using a linear regression analysis test , t test, f test. The data used in this research used a questionnaire instrument and valid data was collected from 100 respondents. The sampling method in this research is a purposive sampling technique. The research results show that the variables of promotion, service quality and user loyalty have a positive and significant influence on the consumer variables of Go-Jek application users.Â Keywords: Promotion, Service Quality, User Loyalty